Per-Anal Endoscopic Myotomy as Rescue Therapy for Hirschsprung Disease After Unsuccessful Surgical Myectomy. Issue 4 (7th April 2022) - Bandres, Dervis; Prada, Carlos; Soto, José; Dávila, Marielvis; Bandres, Maria; García, Victoria
ABSTRACT: Hirschsprung disease (HD) may affect short, ultrashort, or long segments of the rectum. Invasive endoscopy has gained popularity in its treatment. We report a case of a 9-year-old girl diagnosed with HD at 4-year-old, at which time she underwent a myectomy. Nonetheless, because of the persistence of clinical symptoms such as bowel movements every 5–7 days and abdominal distension, per-anal endoscopic myotomy was recommended. An anterograde myotomy in the posterior wall was performed to the circular layer of the muscularis propria. At the 3-year follow-up, she has continued daily bowel movements without laxatives.